2000
DOI: 10.1207/s15327027hc1202_4
|View full text |Cite
|
Sign up to set email alerts
|

Consumers as Educators: Implementation of Patient Feedback in General Practice Training

Abstract: There is growing interest in the adoption of patient-based assessments for the training of general practitioners. Consumers are in a unique position to comment on the quality of the doctor-patient interaction. Involving consumers as partners with general practice (GP) registrars and GP educators in the development of a patient feedback instrument enhances the relevance and acceptability of consumers as educators in GP training. It also demonstrates that social and medical agendas can be harmonized. Two patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
1
21
0
2
Order By: Relevance
“…1, 12 Falvo and Smith found that incorporating patient feedback into a resident evaluation system changed resident behavior and increased the awareness that patient feelings are important when providing medical care. 1,13 Outside of surgery, others have shown that patient satisfaction surveys can provide a useful assessment tool for evaluating residents in many ACGME core competencies, including Interpersonal and Communication Skills and Professionalism 14 and that instituting a communication curriculum for trainees has been shown to increase patient satisfaction. 11 The data from our study demonstrate that residents do influence patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 12 Falvo and Smith found that incorporating patient feedback into a resident evaluation system changed resident behavior and increased the awareness that patient feelings are important when providing medical care. 1,13 Outside of surgery, others have shown that patient satisfaction surveys can provide a useful assessment tool for evaluating residents in many ACGME core competencies, including Interpersonal and Communication Skills and Professionalism 14 and that instituting a communication curriculum for trainees has been shown to increase patient satisfaction. 11 The data from our study demonstrate that residents do influence patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…1 One of the major purposes of any residency program should be to develop graduates who can communicate effectively with patients. 1 In fact, although residents currently receive little or no feedback from patients, it has been reported that one of the most positive aspects of medical training is the knowledge that patients are satisfied. 1 However, little is known about the impact residents have on patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that an increasing number of doctors elicit patients' perspectives both while care is being given (Barr & Vergun, 2000) and subsequent to delivery. There are even some nascent movements toward including patients' assessments of care in the training of medical practitioners (Greco et al, 2000).…”
Section: Looking To Other Professions: Authorizing Clients In Medicinmentioning
confidence: 99%
“…Inform the patient that the results of his FOBT from the year before had been overlooked (i.e., filed before the physician had reviewed them), and that those results had in fact been positive measured components of caring [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Seven patients participated in a 'think-aloud' cognitive interviewing exercise, as they rated the nine encounters.…”
Section: Medical Errormentioning
confidence: 99%